Community Portrait of Bonne-Espérance - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2012)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.
Keywords: Official Language Minority Community (OLMC)

Community Portrait : New Carlisle - Richardson, Mary; Gauvin-Racine, Joëlle (Community Health and Social Services Network (CHSSN), 2012)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.
Keywords: Official Language Minority Community (OLMC)

Saint Brigid's and its Foundation : A Tradition of Caring Since 1856 - Donovan, Patrick (Jeffery Hale - Saint Brigids (JHSB), 2012)
Excursions have always been part of Saint Brigid’s history. In the summer of 1894, the orphans piled into horse-drawn trams and wagons headed for the rural hinterland of Sainte Foy, where they enjoyed a picnic on Mr. Boyce’s farm. While horse-drawn trams are a thing of the past, and Sainte Foy now has more parking lots than farms, the home’s residents still enjoy trips to see the fall colours, go fishing, or enjoy a spot of shopping. In the following pages, the SAINT BRIGID’S HOME FOUNDATION invites you on a different sort of journey: a trip through time that takes you from the beginnings of the home to the present day.

Society Pages - Morrin Centre (2012)

Society Pages - Morrin Centre (2012)

Society Pages - Morrin Centre (2012)

Society Pages - Morrin Centre (2012)